Lung cancer incidence trends in California by race/ethnicity, histology, sex, and neighborhood socioeconomic status: An analysis spanning 28 years. (June 2017) - Patel, Manali I.; McKinley, Meg; Cheng, Iona; Haile, Robert; Wakelee, Heather; Gomez, Scarlett Lin
Highlights: Lung cancer incidence rates vary by race/ethnicity and socioeconomic status. Males in high socioeconomic areas had the most decrease in lung cancer incidence. Among females, lung cancer incidence rates have not consistently declined. Interventions should target high-risk populations to reduce lung cancer burden. Abstract: Objectives: Lung cancer incidence trends by histology, sex, race/ethnicity, and neighborhood socioeconomic status (nSES) have not been previously reported. We conducted a population-based study of lung cancer incidence over three peri -censal periods: 1988–1992, 1998–2002, and 2008–2012. Materials and methods: We abstracted lung cancer cases from the California Cancer Registry and used US Census and American Community Survey data to develop multidimensional nSES indices for each census period. We calculated nSES tertile-specific incidence rates and rate ratios for each peri -censal period and used incidence rate ratios (IRR) to assess changes in rates from 1988 to 1992 to 1998–2002 and 2008–2012. Results: There were a total of 231, 205 lung cancer cases. Males: Among males, incidence rates of lung cancer decreased over time, all race/ethnicities, and all nSES tertiles, with larger declines among males in higher nSES areas. Rates either declined or were stable for adenocarcinoma, with larger declines for other histologic subtypes. Females: Among females, declines in incidence rates of lung cancer were more pronounced for females in higher nSES areas, but diverged more so than for males, with variations by histology and race/ethnicity. Incidence rates of adenocarcinoma increased over time among all females, with greater increase among females in low nSES areas. Conclusions: Our findings demonstrate differences in incidence trends over three decades by histology, gender, race/ethnicity, and nSES. While incidence rates consistently declined over time for males, there were greater declines in incidence for high nSES populations. In contrast, among females, there was evidence of increases in lung cancer incidence among low SES API females, and for adenocarcinoma.